The study on the effect of different levels of zeolit and water stress on growth, development and essential oil content of moldavian balm (Dracocephalum moldavica L.) - Gholizadeh, Asa; Mohd Soom, Mohd Amin; Abdul Rahim, Anuar; Esfahani, Masoud; Saberioon, Mohammadmehdi (Science Publications, 2010)
Problem statement: In order to meet the ever increasing demand of medicinal plants, for the indigenous systems of medicine as well as for the pharmaceutical industry, some medicinal plants need to be cultivated commercially and moldavian balm (Dracocephalum moldavica) is one of them. Approach: To determine the effects of zeolite and water stress on aforementioned plants phisiomorphological characteristics, an experiment was conducted with applying four zeolite levels and three water discharge levels during plant growth. Some growth and development parameters were measured. Results: Summarized that, zeolite did not have any significant effect on plant height and number of internodes but had, on the other traits. There were not a significant effect of water discharge on plant height, number of flowers and number of internodes but its effect on the flowering time and essential oil content was significant. Moreover, there was not an interaction between zeolite and water stress on number of flowers and number of internodes but this interaction was significant on the other parameters. Conclusions/Recommendations: Finally, 2 g zeolite with 50% water losses was recommended to obtain higher essential oil. Additional researches are needed to confirm the results for data from other fields and crops.